Effectiveness of Kinesiotherapy in the Treatment of Achilles Tendinopathy-A Narrative Review - Robert Trybulski; Jarosław Muracki; Mieszko Podleśny; Andriy Vovkanych; Adrian Kużdżał (MDPI AG, 2024)
This narrative review of kinesiotherapy methods in the treatment of Achilles tendinopathy (AT) encompassed a diverse range of studies, including athletes and untrained people, healthy or injured, undergoing kinesiotherapy treatments. Most experimental studies (86%) reported results related to pain perception, 27% to the range of motion, and 27% to biomechanical assessment. However, the studies showed notable heterogeneity in the outcomes associated with the interventions, and, in this review of kinesiotherapy protocols for AT, a prominent observation emerged regarding their efficacy, suggesting a more favorable impact on pain and tendon stiffness management when comparing the measured parameters between the trained and untrained groups. The importance of tailoring the treatment approach based on the individual's athletic background and conditioning status is underscored. There is a need for personalized rehabilitation strategies in athletic populations. The average duration of kinesiotherapy in the treatment of tendinopathy was 15.3 weeks. This observation underscores the potential of kinesiotherapy interventions as a viable treatment option for individuals with Achilles tendon issues. These findings underscore the urgent need for further research to provide stakeholders with more comprehensive directions for future studies. The results may be helpful for doctors, physiotherapists, trainers, and researchers interested in this topic.